2013
DOI: 10.1007/s00345-013-1160-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of post-operative intravesical recurrence and oncological outcomes after open versus laparoscopic nephroureterectomy for upper urinary tract urothelial carcinoma

Abstract: There existed no significant difference of intravesical recurrence and CSS between patients after ONU and LNU. Conclusively, laparoscopic radical nephroureterectomy did not present superiority to open management for patients with UUT-UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 23 publications
2
23
0
2
Order By: Relevance
“…A total of 1,037 articles were excluded upon examination of the titles and abstracts, while the full text of 315 articles was evaluated. In accordance with all previously mentioned inclusion criteria, a final selection of 79 articles was made [912, 1892]; any discrepancies between the two evaluations were resolved. The PRISMA flow chart depicting the process for the systematic literature search and selection of the studies is shown in Figure 5.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 1,037 articles were excluded upon examination of the titles and abstracts, while the full text of 315 articles was evaluated. In accordance with all previously mentioned inclusion criteria, a final selection of 79 articles was made [912, 1892]; any discrepancies between the two evaluations were resolved. The PRISMA flow chart depicting the process for the systematic literature search and selection of the studies is shown in Figure 5.…”
Section: Methodsmentioning
confidence: 99%
“…Raman et al (34) reached the same conclusion in their study including 1249 patients, and they also reported that tumor location in the ureter or pelvis did not affect recurrence or survival. Zou et al (35) compared open (n=101) and laparoscopic (n=21) nephroureterectomies and reported that surgical technique did not affect intravesical recurrence or mortality, while history of preoperative tumor in the bladder and presence of hydronephrosis were associated with intravesical recurrence, and tumor pathology (stage, grade, and lymphovascular invasion) was a significant predictor of cancer-specific mortality. Two studies with follow-up periods of 5 years (36) and 13.6 years (37) are noteworthy in terms of the long-term follow-up and survival comparisons between laparoscopic and open NU.…”
Section: Robotic Radical Nephroureterectomymentioning
confidence: 99%
“…• la multifocalité tumorale [33,69,88,89] ; • la localisation urétérale, et plus particulièrement le tiers distal de l'uretère [85,[89][90][91][92][93][94] ; • stade tumoral : un stade tumoral musculo-invasif (≥ pT2) était significativement associé à un taux de récidive vési-cale important [85,[89][90][91][92][93][94] ;…”
Section: Facteurs Pronostiques Postopératoires De Récidive Vésicaleunclassified
“…• les résultats concernant l'impact de la taille tumorale sur les récidives vésicales sont contradictoires dans la littérature [92,94]. Pour ces mêmes auteurs, la présence d'une nécrose tumorale étendue ≥ 10 % pourrait être un élément péjoratif de cette survie [92,94], • un IMC > 30 kg/m 2 pourrait être associé à des récidives vésicales plus fréquentes de part la difficulté à obtenir une collerette vésicale chez les patients obèses [18], • une surexpression de Ki67 au sein de la lésion tumorale ainsi que l'amplification 20q13.2 pourraient constituer des facteurs de risque de récidive vésicale après NUT [95,96], • un nomogramme permettant de prédire la survie sans récidive vésicale des patients après NUT a été récemment proposé [85].…”
Section: Facteurs Pronostiques Postopératoires De Récidive Vésicaleunclassified